2004
DOI: 10.1002/jmv.20201
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of apoptosis during HTLV‐1‐mediated immortalization process in vitro

Abstract: Suppression of apoptosis has been proposed as a mechanism involved in the transforming action of human T-cell leukemia/lymphotropic virus type-1 (HTLV-1). However, there is evidence that HTLV-1 and its protein Tax also induce apoptosis. To resolve this apparent paradox, apoptosis was monitored in primary cultures of peripheral blood lymphocytes (PBLs) from healthy donors, following HTLV-1 infection in vitro. High levels of apoptosis in HTLV-1 infected cultures during the first weeks after infection were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, doses Ͻ6.0 M proved to be highly specific for PKC inhibition and kept the viability of PBLs and Jurkat mostly at basal levels. Furthermore, MT-2 cells were surprisingly resilient to rottlerin-induced apoptosis (Ͼ100 M), probably due to the concomitant infection with HTLV-1, which appears to suppress apoptosis as a mechanism involved in the immortalization of the infected lymphocytes (61,62). In fact, although MT-2 cells are usually destroyed by pGeneClip-iPKC-C1 and pGeneClip vectors were used as negative controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, doses Ͻ6.0 M proved to be highly specific for PKC inhibition and kept the viability of PBLs and Jurkat mostly at basal levels. Furthermore, MT-2 cells were surprisingly resilient to rottlerin-induced apoptosis (Ͼ100 M), probably due to the concomitant infection with HTLV-1, which appears to suppress apoptosis as a mechanism involved in the immortalization of the infected lymphocytes (61,62). In fact, although MT-2 cells are usually destroyed by pGeneClip-iPKC-C1 and pGeneClip vectors were used as negative controls.…”
Section: Discussionmentioning
confidence: 99%
“…To shed light into this subject, some of us pioneered the experimental model of HTLV-1 infection in vitro several years ago. Our model consisted of a long-term culture of PBMCs from healthy donors after exposure to irradiated HTLV-1-infected cells as viral donors [80]. We felt that such a model was the best strategy to recapitulate in vitro what occurs naturally in vivo in HTLV-1-infected patients during the long period of immortalization and transformation that could lead to ATL.…”
Section: Latency and Leukemogenesis: Role Of Tax Hbz And Apoptosismentioning
confidence: 99%
“…Indeed, the results of this study showed that the in vitro HTLV-1 infection of mononuclear cells induces a high rate of cell proliferation during the first weeks accompanied by a heightened susceptibility to RCD through apoptosis. Moreover, there is a progressive decrease in cell death rates observed during the long-term culture phase, ultimately leading to cell immortalization [80]. Additionally, in situ hybridization showed that the cells undergoing apoptosis were indeed the infected ones, with HTLV-1 proviral DNA, rather than residual uninfected cells [80].…”
Section: Latency and Leukemogenesis: Role Of Tax Hbz And Apoptosismentioning
confidence: 99%
“…As observed in other neoplasia, the balance between pro and anti apoptotic response is subverted in ATL cells. Preclinical studies have shown that HTLV-1 infection in vitro gives rise, in a first phase, to high proliferation and a concomitant high apoptosis rate in infected cells until, in a successive phase, the selection of immortalized clones lead to outgrowth of cells preferentially exhibiting anti-apoptotic gene expression ( Matteucci et al, 2004 ). Coherently, transformed clones from ATL patients over-express in culture the anti-apoptotic Bcl-2, Bcl-xL, and Bcl-w proteins and exhibit ex vivo a 10- to 20-fold higher sensitivity to navitoclax (ABT-263), an orally bio-available mimetic of the Bcl-2 homology domain 3 small molecule, as compared to non-HTLV-1-associated leukemic cells ( Tse et al, 2008 ).…”
Section: Targeted Biological Therapy For Atlmentioning
confidence: 99%